Numerical Simulation of The Effect of Wind Velocity on The Diffuser Augmented Wind Turbines Performance - Irawan, Yosua Heru; Harianto, Harianto (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2019)
The study was conducted on GE 1.5 XLE wind turbine blades with a blade length of 4.32 m. This study uses a numerical simulation method with the help of ANSYS Workbench 19 software. Simulation is carried out at wind speeds of 3 m/s, 5 m/s, and 8 m/s. The DAWT (Difuser Augmented Wind Turbines) research model uses the same wind turbine blade as a conventional wind turbine model which is the same GE 1.5 XLE model. The size of the diffuser added to the construction of the wind turbine is 9 m in addition to flanged on the side of the inlet and outlet diffuser.Based on numerical simulations carried out, for wind speeds of 3 m/s, the highest increase in DAWT performance is 115.6%. For wind speeds of 5 m/s, the highest increase in DAWT performance is 99.2%. For wind speeds of 7 m/s, the highest increase in DAWT performance is 91.8%. Based on the simulation results it can be said that the addition of diffuser in the construction of wind turbines will produce effective performance at wind speeds of 3 m/s. The increase in DAWT performance is relatively small on TSR 1-4, and some even experience a decrease in performance. So that it can be said that DAWT is not suggested to be operated on a low TSR, DAWT is recommended to operate above TSR 5.